How the interpretation of match statistics affects player performance - Bedford, A.; Barnett, T.; Pollard, G.; Pollard, G. (Medicine and Science in Tennis, 2010)
Commentators often refer to match statistics during a live match to make an assessment as to how the players are performing. For example, one player may have converted 80% of break point opportunities compared to 10% for the other player, and this is reflected in the scoreboard. At the completion of the match, the coaches and players are likely to use the match statistics to assess performance. Therefore, it is important to interpret match statistics correctly as misinterpretation could affect future performance. Andre Agassi lost to Marat Safin at the 2004 Australian Open semi-finals, even though Agassi won more points overall (171 for Agassi compared to 170 for Safin). This could be interpreted after the match as Agassi being "unlucky" in the sense that Agassi really performed better on the day by winning more points overall and lost as a result of two close tiebreaker sets that went in favor of Safin. The logic in the previous sentence is flawed. It is often the case that the weaker player serves more often and therefore has more opportunity to win more points. Therefore, a comparison of the percentage of points won on serve by each player should be used to interpret whether a player was "unlucky" to lose the match. As it turned out, Safin won a higher percentage of points on serve with 67.7% compared to 66.1% for Agassi.